Development of two UAVs for volcano studies in southern peru - Apaza, J.; Scipión, D.; Lume, D.; Saito, C. (Institute of Electrical and Electronics Engineers, 2017)
The development of Unmanned Aerial Vehicles (UAVs) has gained importance over the last few years due to the innovations brought to farming, architecture, and/or medicine. A novel field where they have been used is volcanology for its long-distance control and the possibility to add multiple sensors for sensing volcano parameters. Two UAVs will be constructed: a multi-rotor (quadcopter) and a fix wing airplane for studying the most active volcano in Peru, the Ubinas. The objective is to get important and useful volcano data without risking the lives of researchers. The quadcopter will be used for image capturing and video recording of the plume, while the airplane will fly close or through to the volcanic plume measuring temperature, humidity, carbon dioxide, sulfuric dioxide, and hydrogen sulfide.
Keywords: Volcano; Quadcopter; Plume; Airplane; Remote sensing; Computer science; Environmental science; Geology; Earth science; Aerospace engineering; Aeronautics; Meteorology; Engineering; Seismology; Geography; https://purl.org/pe-repo/ocde/ford#2.01.01